Anti‐inflammatory effects of the novel inhaled phosphodiesterase type 4 inhibitor CHF6001 on virus‐inducible cytokines - Edwards, Michael R. (Pharmacol Res Perspect, 2016)
Respiratory virus infections precipitate asthma and chronic obstructive pulmonary disease (COPD) exacerbations, with most exacerbations due to rhinovirus infection. Both asthma and COPD exacerbations are not well controlled by steroid therapies, and there is a much research interest in finding improved therapies or combinations of therapies for controlling exacerbations. CHF6001 is a new, inhaled highly potent and selective phosphodiesterase type 4 (PDE4) inhibitor. Using in vitro human bronchial epithelial cells (BEAS‐2B), we investigated the potential anti‐inflammatory effects of CHF6001 on rhinovirus (RV1B)‐induced cytokines. Cytokine mRNA was measured by real‐time PCR, while protein release was measured by ELISA. CHF6001 was used in a 7‐point dose–response curve (1000–0.001 nmol/L) as a 1.5‐h pretreatment prior to infection in comparison with roflumilast. Both roflumilast and CHF6001 reduced RV1B‐induced IL‐8, IL‐29, IP‐10, and RANTES mRNA and protein in a concentration‐dependent manner. Generally, CHF6001 was 13‐ to 16‐fold more potent (subnanomolar EC (50) values) than roflumilast at reducing IL‐8, IL‐29, IP‐10, and RANTES mRNA and protein release, but had similar efficacies. In combination with the steroid fluticasone propionate (1 nmol/L), CHF6001 had additive effects, significantly reducing RV‐induced cytokines when compared with steroid or CHF6001 alone. Combined low‐dose steroid and low‐dose CHF6001 had a similar efficacy as high‐dose steroid or CHF6001 alone, indicating the combination had steroid and PDE4 inhibitor sparing effects. Overall results indicate that PDE4 inhibitors have anti‐inflammatory activity against virus‐induced inflammatory mediators and that CHF6001 is more potent than roflumilast.